The Impact of the First Peak of the COVID-19 Pandemic on a Paediatric Ophthalmology Service in the United Kingdom: Experience from Alder Hey Children's Hospital. Issue 1 (25th March 2021) - Wood, Megan; Gray, Judith; Raj, Ankur; Gonzalez-Martin, Jose; Yeo, Damien C.M.
Objective: The COVID-19 pandemic has led to significant service loss across the NHS, and ophthalmology is one of the greatest affected specialties. We attempt to quantify the impact of the first peak of the COVID-19 pandemic on a paediatric ophthalmology unit in a children's hospital in the United Kingdom (UK) and report lessons learnt to aid in the recovery of the service. Methods and Analysis: Two eight-week periods of clinical activity were compared; one during the first UK peak of the COVID-19 pandemic and the other during a similar period the previous year. Four areas of clinical activity were included in the study: outpatient clinic appointments, theatre activity, outpatient referrals to ophthalmology and ward reviews. Appointment data was collected from departmental databases. Results: During the first peak of the pandemic, outpatient clinic appointments were reduced by 87.2%, ophthalmic surgery by 90.9%, outpatient referrals to ophthalmology by 50.2% and ward reviews by 50%. The number of actual cancelled appointments was 1377, of which 6.8% were triaged as suitable for teleophthalmology. Conclusion: The COVID-19 pandemic has dramatically restricted clinical activity in the ophthalmology service. Paediatric ophthalmology is vulnerable to capacity issues and the consequences of delayed or cancelled appointments. Departments must adapt quickly and maximise capacity to help reduce the backlog and treat patients effectively and safely. Solutions such as teleophthalmology have potential although can be difficult in the paediatric population.